A luminous blue kilonova and an off-axis jet from a compact binary merger at z = 0.1341. Issue 1 (December 2018) - Troja, E.; Ryan, G.; Piro, L.; Eerten, H.; Cenko, S.; Yoon, Y.; Lee, S.-K.; Im, M.; Sakamoto, T.; Gatkine, P.; Kutyrev, A.; Veilleux, S.
Abstract The recent discovery of a gamma-ray burst (GRB) coincident with the gravitational-wave (GW) event GW170817 revealed the existence of a population of low-luminosity short duration gamma-ray transients produced by neutron star mergers in the nearby Universe. These events could be routinely detected by existing gamma-ray monitors, yet previous observations failed to identify them without the aid of GW triggers. Here we show that GRB150101B is an analogue of GRB170817A located at a cosmological distance. GRB150101B is a faint short burst characterized by a bright optical counterpart and a long-lived X-ray afterglow. These properties are unusual for standard short GRBs and are instead consistent with an explosion viewed off-axis: the optical light is produced by a luminous kilonova, while the observed X-rays trace the GRB afterglow viewed at an angle of 13°. Our findings suggest that these properties could be common among future electromagnetic counterparts of GW sources. A faint gamma-ray burst (GRB 170817A) has been recently detected in coincidence with the gravitational wave (GW) event GW 170817. Here, the authors report that another faint short GRB at a cosmological distance (GRB150101B) and its late time emission are analogous to the neutron star merger event GRB 170817A.